The morphology of the coronary sinus in patients with congenitally corrected transposition: implications for cardiac catheterisation and re-synchronisation therapy. (3rd March 2015) - Aiello, Vera D.; Ferreira, Flávia C. N.; Scanavacca, Mauricio I.; Anderson, Robert H.; D'Avila, André
Abstract: Patients with congenitally corrected transposition frequently benefit from re-synchronisation therapy or ablation procedures. This is likely to require catheterisation of the coronary sinus. Its anatomy, however, is not always appreciated, despite being well-described. With this caveat in mind, we have evaluated its location and structure in hearts with congenitally corrected transposition in order to reinforce the guidance needed by the cardiac interventionist. We dissected and inspected the coronary sinus, the oblique vein of the left atrium, and the left-sided-circumflex venous channel in eight heart specimens with corrected transposition and eight controls, measuring the orifice and length of the sinus and the atrioventricular valves. In two-thirds of the malformed hearts, the sinus deviated from its anticipated course in the atrioventricular groove, ascending obliquely on the left atrial inferior wall to meet the left oblique vein. The maximal deviation coincided in all hearts with the point where the left oblique vein joined the left-sided-circumflex vein to form the coronary sinus. We describe a circumflex vein, rather than the great cardiac vein, as the latter venous channel is right-sided in the setting of corrected transposition. The length of the sinus correlated positively with the diameter of the tricuspid valve (p=0.02). Compared with controls, the left oblique vein in the malformed hearts joined the circumflex venous channel significantly closer to the mouth of the sinus. The unexpected course of the coronary sinus in corrected transposition and the naming of the cardiac veins have important implications for venous cannulation and interpretation of images.